Specifična poraba toplote kot funkcija storilnosti potisne peči - Kolenko, Tomaž (Kovine zlitine tehnologije, 1998)
A new method of calculation of the specific heat consumption and thermal efficiency of continuous reheating processes is shown. Using the example of a pusher-type-furnace, it is shown how both parameters of fuel efficiency utilisation may be calculated in real time. In this manner the dependency of the specific heat consumption as a function of the furnace throughput can be established for different operating conditions in a reasonable length of time.
Keywords: toplota; izkoristek; plošče; peči